Is serum biotinidase enzyme activity a potential marker of perturbed glucose and lipid metabolism?. Issue 1 (6th October 2020) - Forny, Patrick; Burda, Patricie; Bode, Peter; Rohrbach, Marianne
Abstract: Glycogen storage diseases (GSDs) belong to the group of inborn errors of carbohydrate metabolism. Hepatic GSDs predominantly involve the liver and most present with hepatomegaly. Biochemically they show known disturbances in glucose and fatty acids metabolism, namely fasting hypoglycaemia and increased triglycerides. Additionally, increased biotinidase (BTD) enzyme activity has been shown to be associated with many GSD types, whereas the mechanism by which BTD enzyme activity is altered remains unknown so far. We aimed to delineate changes in gluconeogenesis and fatty acid synthesis, potentially explaining raised BTD enzyme activity, by using liver (specimens from 2 patients) and serum samples of GSD Ia and GSD IV patients. By expression analysis of genes involved in gluconeogenesis, we ascertained increased levels of phosphoenolpyruvate carboxykinase and fructose‐1, 6‐biphosphatase, indicating an increased flux through the gluconeogenic pathway. Additionally, we found increased gene expression of the biotin‐dependent pyruvate and acetyl‐CoA carboxylases, providing substrate for gluconeogenesis and increased fatty acid synthesis. We also observed a significant linear correlation between BTD enzyme activity and triglyceride levels in a cohort of GSD Ia patients. The results of this pilot study suggest that enhancement of BTD activity might serve the purpose of providing extra cofactor to the carboxylase enzymes as an adjustment to disturbed glucose and fatty acid metabolism. Future studies involving a higher number of samples should aim at confirming the here proposed mechanism, which extends the application of BTD enzyme activity measurement beyond its diagnostic purpose in suspected GSD, and opens up possibilities for its use as a sensor for increased gluconeogenesis and fatty acid synthesis.